Peran Pendekatan STEM (Science, Technology, Engineering, and Mathematic) dalam Pembelajaran - Laila, Sherly; Wardani, Rini Sri; Umayah, Aura Rhomatul; Huda, Muhammad Khomarul; Hutahuruk, Ahmad Fakhri (Mahesa Research Center, 2024)
The STEM approach is an affective learning method that can improve the quality of science education by integrating various elements of science holistically, so that it can improve students’ cognitive, psychomotor and affective skills. This study aims to examine the role of the STEM approach in learning and its impact in growing students’ interest in science and technology, as well as preparing them to face the challenges of the world of work in the future. The method used is content analysis from various literature related to the implementation of STEM in learning. The results of the study show that the application of STEM is able to integrate various scientific disciplines and have a positive impact on students’ skills, so this approach is recommended to be applied in learning.